2019
DOI: 10.1016/j.biocon.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

High critical forest habitat thresholds of native bird communities in Afrotropical agroforestry landscapes

Abstract: Our knowledge on the nature of forest species responses to deforestation remains ambiguous. Moreover, most previous research took place in fragmented landscapes or did not take into account the diversity of ecological features among the studied species. Understanding the relationship between forest cover and functional guilds inside a bird community may serve as a valuable tool to assess how much forest is necessary to conserve significant portions of forest species. We sampled birds (198 species, 6 883 encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…Birds are good indicators of habitat quality (Kupsch et al, 2019), with groups such as insectivores showing high sensitivity to habitat degradation (Karp et al, 2011;Powell et al, 2015;Stratford & Stouffer, 2013;Tchoumbou et al, 2020;Wolfe et al, 2015). In the tropics, many bird species depend strictly on microhabitats often only present in pristine forest (forest specialists; Stratford & Stouffer, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birds are good indicators of habitat quality (Kupsch et al, 2019), with groups such as insectivores showing high sensitivity to habitat degradation (Karp et al, 2011;Powell et al, 2015;Stratford & Stouffer, 2013;Tchoumbou et al, 2020;Wolfe et al, 2015). In the tropics, many bird species depend strictly on microhabitats often only present in pristine forest (forest specialists; Stratford & Stouffer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we know little regarding vertebrate communities, and how they are affected by farm management practices (Schroth & Harvey, 2007;Sekercioglu, 2012). The notable exceptions are Waltert et al (2005) and Kupsch et al (2019), who surveyed birds across a gradient of land-use intensification which included some cocoa plots, and found that although species richness did not decrease with increasing habitat modification, community composition was significantly affected, with a decrease in abundance of largebodied frugivores and terrestrial insectivores.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that Grey Parrots are at least to some extent able to adapt to substantial habitat alterations, if large trees are maintained as breeding and roosting sites. Our study highlights the urgent need for a stronger prioritization of Grey Parrots within conservation programmes and the development of multi-facetted conservation strategies containing: (i) effective eco-guard patrolling schemes in the Korup region (Astaras et al 2017), (ii) a consequent inhibition of illegal pet trade routes and markets in the entire region of SW Cameroon/SE Nigeria, and (iii) the promotion of traditional agroforestry practices in preference to monocultural agriculture (Kupsch et al 2019). Such steps along with the implementation of CITES will help prevent further over-exploitation and future declines of wild populations in the region.…”
Section: Resultsmentioning
confidence: 99%
“…These were Ikondo kondo 1 and Fabe, which are located c.7.5 km and 15 km north-east of Mundemba, respectively (Figure 1). These villages are mainly inhabited by traditional smallholder families, who plant a mixture of subsistence and cash crops in and around their villages within a landscape dominated by remaining primary and secondary forests (Kupsch et al 2019). Fire is often used to clear small areas inside forest, often in the shade of old trees, e.g.…”
Section: Agroforestry Matricesmentioning
confidence: 99%
See 1 more Smart Citation